Answer: 57.8
Step-by-step explanation: you can eithere do 68 % 85 or other way which i forgot
Answer:
The first step is to divide all the terms by the coefficient of
which is 2.
The solutions to the quadratic equation
are:
![x=\frac{5}{4}+i\frac{\sqrt{511}}{4},\:x=\frac{5}{4}-i\frac{\sqrt{511}}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B4%7D%2Bi%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D%2C%5C%3Ax%3D%5Cfrac%7B5%7D%7B4%7D-i%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D)
Step-by-step explanation:
Considering the equation
![2x^2\:-\:5x\:+\:67\:=\:0](https://tex.z-dn.net/?f=2x%5E2%5C%3A-%5C%3A5x%5C%3A%2B%5C%3A67%5C%3A%3D%5C%3A0)
The first step is to divide all the terms by the coefficient of
which is 2.
so
![\frac{2x^2-5x}{2}=\frac{-67}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E2-5x%7D%7B2%7D%3D%5Cfrac%7B-67%7D%7B2%7D)
![x^2-\frac{5x}{2}=-\frac{67}{2}](https://tex.z-dn.net/?f=x%5E2-%5Cfrac%7B5x%7D%7B2%7D%3D-%5Cfrac%7B67%7D%7B2%7D)
Lets now solve the equation by completeing the remaining steps
Write equation in the form: ![x^2+2ax+a^2=\left(x+a\right)^2](https://tex.z-dn.net/?f=x%5E2%2B2ax%2Ba%5E2%3D%5Cleft%28x%2Ba%5Cright%29%5E2)
Solving for
,
![2ax=-\frac{5}{2}x](https://tex.z-dn.net/?f=2ax%3D-%5Cfrac%7B5%7D%7B2%7Dx)
![a=-\frac{5}{4}](https://tex.z-dn.net/?f=a%3D-%5Cfrac%7B5%7D%7B4%7D)
![\mathrm{Add\:}a^2=\left(-\frac{5}{4}\right)^2\mathrm{\:to\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3A%7Da%5E2%3D%5Cleft%28-%5Cfrac%7B5%7D%7B4%7D%5Cright%29%5E2%5Cmathrm%7B%5C%3Ato%5C%3Aboth%5C%3Asides%7D)
![x^2-\frac{5x}{2}+\left(-\frac{5}{4}\right)^2=-\frac{67}{2}+\left(-\frac{5}{4}\right)^2](https://tex.z-dn.net/?f=x%5E2-%5Cfrac%7B5x%7D%7B2%7D%2B%5Cleft%28-%5Cfrac%7B5%7D%7B4%7D%5Cright%29%5E2%3D-%5Cfrac%7B67%7D%7B2%7D%2B%5Cleft%28-%5Cfrac%7B5%7D%7B4%7D%5Cright%29%5E2)
![x^2-\frac{5x}{2}+\left(-\frac{5}{4}\right)^2=-\frac{511}{16}](https://tex.z-dn.net/?f=x%5E2-%5Cfrac%7B5x%7D%7B2%7D%2B%5Cleft%28-%5Cfrac%7B5%7D%7B4%7D%5Cright%29%5E2%3D-%5Cfrac%7B511%7D%7B16%7D)
Completing the square
![\left(x-\frac{5}{4}\right)^2=-\frac{511}{16}](https://tex.z-dn.net/?f=%5Cleft%28x-%5Cfrac%7B5%7D%7B4%7D%5Cright%29%5E2%3D-%5Cfrac%7B511%7D%7B16%7D)
Since, you had required to know the first step in completing the square for the equation above, I hope you have got the point, but let me quickly solve the remaining solution.
For
the solution are ![f\left(x\right)=\sqrt{a},\:-\sqrt{a}](https://tex.z-dn.net/?f=f%5Cleft%28x%5Cright%29%3D%5Csqrt%7Ba%7D%2C%5C%3A-%5Csqrt%7Ba%7D)
Solving
![x-\frac{5}{4}=\sqrt{-\frac{511}{16}}](https://tex.z-dn.net/?f=x-%5Cfrac%7B5%7D%7B4%7D%3D%5Csqrt%7B-%5Cfrac%7B511%7D%7B16%7D%7D)
![x-\frac{5}{4}=\sqrt{-1}\sqrt{\frac{511}{16}}](https://tex.z-dn.net/?f=x-%5Cfrac%7B5%7D%7B4%7D%3D%5Csqrt%7B-1%7D%5Csqrt%7B%5Cfrac%7B511%7D%7B16%7D%7D)
∵ Applying imaginary number rule ![\sqrt{-1}=i](https://tex.z-dn.net/?f=%5Csqrt%7B-1%7D%3Di)
![x-\frac{5}{4}=i\frac{\sqrt{511}}{\sqrt{16}}](https://tex.z-dn.net/?f=x-%5Cfrac%7B5%7D%7B4%7D%3Di%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B%5Csqrt%7B16%7D%7D)
![-\frac{5}{4}=i\frac{\sqrt{511}}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B4%7D%3Di%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D)
![x=\frac{5}{4}+i\frac{\sqrt{511}}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B4%7D%2Bi%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D)
Similarly, solving
![x-\frac{5}{4}=-\sqrt{-\frac{511}{16}}](https://tex.z-dn.net/?f=x-%5Cfrac%7B5%7D%7B4%7D%3D-%5Csqrt%7B-%5Cfrac%7B511%7D%7B16%7D%7D)
∵ Applying imaginary number rule ![\sqrt{-1}=i](https://tex.z-dn.net/?f=%5Csqrt%7B-1%7D%3Di)
![x=\frac{5}{4}-i\frac{\sqrt{511}}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B4%7D-i%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D)
Therefore, the solutions to the quadratic equation are:
![x=\frac{5}{4}+i\frac{\sqrt{511}}{4},\:x=\frac{5}{4}-i\frac{\sqrt{511}}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B5%7D%7B4%7D%2Bi%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D%2C%5C%3Ax%3D%5Cfrac%7B5%7D%7B4%7D-i%5Cfrac%7B%5Csqrt%7B511%7D%7D%7B4%7D)
Answer:
![x \geqslant 2 \: \: \: \: or \: \: \: \: 2 \leqslant x \\](https://tex.z-dn.net/?f=x%20%5Cgeqslant%202%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20or%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%202%20%5Cleqslant%20x%20%5C%5C%20)
Step-by-step explanation:
![- 6 \geqslant 10 - 8x \\ - 6 - 10 \geqslant - 8x \\ - 16x \geqslant - 8x \\ \frac{ - 16}{ - 8} \leqslant x \\ 2 \leqslant x](https://tex.z-dn.net/?f=%20-%206%20%5Cgeqslant%2010%20-%208x%20%5C%5C%20-%206%20-%2010%20%20%5Cgeqslant%20%20-%208x%20%5C%5C%20%20-%2016x%20%5Cgeqslant%20%20-%208x%20%5C%5C%20%20%5Cfrac%7B%20-%2016%7D%7B%20-%208%7D%20%20%5Cleqslant%20x%20%5C%5C%202%20%5Cleqslant%20x)
The vertex will be (1,4) I use a graphing calculator to find this answer